Thermoelectric Properties of Nanocrystalline Silicon from a Scaled‐Up Synthesis Plant1. Issue 5 (20th December 2012) - Kessler, Victor; Gautam, Devendraprakash; Hülser, Tim; Spree, Mathias; Theissmann, Ralf; Winterer, Markus; Wiggers, Hartmut; Schierning, Gabi; Schmechel, Roland
Abstract Silicon based thermoelectrics are promising candidates for high temperature energy scavenging applications. We present the properties of thermoelectrics made from highly boron doped silicon nanoparticles. The particles were produced by a continuous gas phase process in a scaled‐up synthesis plant enabling production rates in the kg h−1 regime. The silicon nanoparticles were compacted by direct current assisted sintering to yield nanocrystalline bulk silicon with average crystallite size between 40 and 80 nm and relative densities above 97% of the density of single crystalline silicon. The influence of the sintering temperature on the thermoelectric properties is investigated. It was found that high sintering temperatures are beneficial for an enhancement of the power factor, while the thermal conductivity was only moderately affected. The optimization of the compaction procedure with respect to the transport properties leads to zT values of the p‐type nanosilicon of 0.32 at 700 °C, demonstrating the potential of our method.